A LabVIEW Program for Controlling Pressure and Temperature in Rapid-Quench Cold-Seal Experimental Apparatus - Kast, Jacob (My University, 2014)
The purpose of this study was to conduct experiments pertaining to rapid-quench cold-seal pressure vessels. They are ideal for conducting experiments at conditions relevant to the Earth's upper crust. Rapid quenches are achieved by lowering the experimental charge from a hot vessel (placed inside a furnace) into an underlying cold vessel through the use of a magnetically levitated elevator rod. We employ LabVIEW software to monitor, record, and control, for the first time in cold-seal apparatus, both pressure and temperature by applying small temperature adjustments to heating tape wrapped around the cold vessels.
Color poster with text, images, and charts.
Keywords: Geology; Cold-seal experimental apparatus; LabVIEW software; Posters